MENUMBUHKAN UMKM DENGAN PEMANFAATAN POTENSI DESA - Dina Khairuna Siregar; Diah Permata Sari; Indra Pangestu; Aldo Alif Fisa Pangestu; Retno Wahyuningrum (Amal Insani Foundation, 2022)
One sector that has an important role in the economic recovery process is MSMEs. However, most of the MSMEs in Indonesia are still run traditionally. In addition, there are some common problems that are often experienced by MSMEs, namely limited capital, not yet having a clear legal entity, lack of product innovation and many MSME actors still not technologically savvy. Kencana Harapan Village is a village located in Lebak Wangi District, Serang Regency, Banten. Kencana Harapan Village is a rice field area, with the main natural resource being rice, where the economy of the Kencana Harapan village community is relatively minimal and not yet prosperous. This outreach activity is expected to enable the residents of Kencana Harapan Village to gain knowledge to create MSMEs, manage MSME capital and how to market MSME products according to the times with the digital era, so that it is expected to improve the economy of local residents. The method of this service activity uses the lecture, discussion and question and answer method. The results of this outreach activity increased the level of knowledge of the people of Kencana Haraoan Village about the role of MSMEs in the Indonesian economy